Birth and Survival of Graduate Enterprises an Universities - Ondoš, S.; Polonyová, E.; Ely, Philip (Technical University of Košice, 2015)
Arguably, local and national economic ecosystems rely on the influence of higher education institutions who - in turn - influence the birth and survival of graduate businesses. The first kind of influence can be rooted in academic research and development activities: innovators within academia transform the scientific advancements into spinoff companies, delivering a hypothetically significant market advantage. The second kind of influence can be related to the university graduates: new businesses are created providing graduate start-ups with competitive advantage built on new knowledge and skills developed during learning programmes. These graduate enterprises - once born - differ in their likelihood of survival, the number of employees they hire and in volume of turnover. The location of these start-ups (both within knowledge domains and geographic space) may be systematically influencing both birth intensity and survival trajectory. For example, urban areas - with more competition, variety in demand, and with a historical record of higher entrepreneurial activity - are often seen as providing the right environment for generating more successful entrepreneurs. In other regions, the lack of employment opportunities prevents certain enterprises from being born into the local economy; whilst at the same time promotes entrepreneurship founded in a necessity to create one's own job. Other locations also differ in availability of initial investment resources - again inhibiting or encouraging start-ups. With these local conditions in mind, we aim to question the survival rate of enterprises located in more and less favourable settings and explore the role of universities in this context as institutions expected to play a positive role in the improved business survival. We attempt to link the volume and orientation of academic research and development activities with graduate enterprises, analysing how certain research domains may be more effective compared to others in transferring knowledge and skills into the marketplace. We also provide a review of the local factors outlined above and propose a design for the econometric testing of university influence on graduate start-ups in the United Kingdom.